BETA: Normative to Positive Statements in Kenya - Ouma, Denis (International Journal of Economics, Business and Innovation Research, 2025)
The support of economic models to a country’s economic agenda and vice versa is not well defined in most developing economies. However, some empirical findings suggest that with commercially viable avenues and practical economic models, sector-led economic and social development could be stimulated by adopted economic models. This study identifies the impact of bottoms up economic models on the Kenyan development trajectory. The five pillar industries: agriculture, industry, housing, healthcare and MSME are used as variables of results. Discussions on the bottoms up and top down models are employed. The period (2023-2025) is used for analytical discussion. With a response rate of 60% from the targeted 28275 households, the results show that although resources distributed through BETA model were stimulants to the five pillars, sectoral specific initiatives incorporating aspects of top down approaches were vital. The study further shows that resource and output of the BETA agenda were affected by time lags. The study recommends that the government could adopt a blended model specific for the different sectors and industry within the pillars and promote effective management of STIIR as this had a positive multiplier effect on all the pillars